DIGITAL EQUIPMENT EFFECTIVE STRESS MEASURE - Deni Nur Shidiq; Jalinas, SKom, MM Jalinas, SKom, MM (Jurnal Sistem Komputer, 2001)
In this thesis, we presented the design of measuring devices, which may be used to measure the effective voltage value of an electrical signal.operation of this measuring instrument used for measuring the effective price of the wavesthat shaped not sequentially, either periodically or non periodic.Designrestricted to the use of measurement of stress waves within the audio frequency region.The main circuit consists of voltage sensor, which at the same time as devidervoltage, the effective price of a modifier of voltage (current) direction, and the last is a digital voltmeter. The output from the sensor circuit signal voltage is still a form similar to the original signal is measured, but the amplitude is different, tailored to local measurements. Modifiers effective price will count valueto floweffective unidirectional signal output from the sensor circuit. The output of this converter circuit becomes the input of digital voltmeter, which is then displayed by the viewer seven sections (seven segment).